2013
DOI: 10.7863/jum.2013.32.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of a Suburethral Sling at the Bladder Neck Is Associated With a Higher Recurrence Rate of Stress Urinary Incontinence

Abstract: Positioning of the suburethral sling at the bladder neck appears to be associated with a higher stress urinary incontinence recurrence rate. Patients with slings located at the proximal and middle urethra had the best postsurgical continence rates. The suburethral sling position had no direct association with de novo urge or voiding symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…Our findings show that when inserting a TOT, beginning the incision at 1/2 the urethral length was more likely to result in a successful outcome than at 1/3 of the urethral length—similar to the standard technique for classical retropubic TVT . One important conclusion of this study, which is consistent with earlier studies, is that patient characteristics (i.e., urethral mobility) ought to be assessed and appropriately matched with the particular functionality of the tapes …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings show that when inserting a TOT, beginning the incision at 1/2 the urethral length was more likely to result in a successful outcome than at 1/3 of the urethral length—similar to the standard technique for classical retropubic TVT . One important conclusion of this study, which is consistent with earlier studies, is that patient characteristics (i.e., urethral mobility) ought to be assessed and appropriately matched with the particular functionality of the tapes …”
Section: Discussionsupporting
confidence: 86%
“…However, Ulmsten's technique was originally developed using technology available over two decades ago that involved radiomorphologic and urodynamic studies. Recent studies utilizing advanced, dynamic medical technology (i.e., 3D/4D ultrasound) found that variations in anatomical/physiological characteristics of women (i.e., urethral length, height of the vaginal sulci, and mobility of the urethra) influence the success of the SUI outcome and the occurrence of postoperative complications …”
Section: Introductionmentioning
confidence: 99%
“…As it was previously mentioned, one of the most important factors influencing the effectiveness of the procedure is the optimal sling location beneath the distal part of urethra (area of high pressure zone). It was shown that proximal (closer to bladder neck) sling implantation is connected with persistent or recurrent incontinence . On the other hand it was also established that adjusting the surgery technique to individual UL (both in case of retropubic and transobturator approach) helps to achieve better results .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors recommended starting the procedure with the vaginal incision 10 mm from the external urethral orifice in order to achieve optimal distal sling location. Further observations demonstrated that proximal sling position (closer to bladder neck) may be one of the causes of failure of anti‐incontinence procedures . Moreover, it has been proved that measuring the UL before the procedure and adjusting the surgical technique to the individual UL provides much better results in sling procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The worst results are obtained when a tape is placed under the proximal urethra, with the failure rate exceeding 50% [52, 54] (Fig. 7).…”
Section: Ultrasound In Management Of Treatment Failure and Complicationsmentioning
confidence: 99%